2016
DOI: 10.4081/jae.2016.519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of six primary tillage implements on energy inputs and residue cover in Central Italy

Abstract: The use of agricultural machinery represents the main aspect contributing to the total energy input in the agricultural system. The study evaluated the energy requirements and the work quality of two conventional (threefurrow plough and spading machine) and of four conservation implements (rotary harrow, subsoiler, disk harrow, combined cultivator) for mediumdeep primary tillage in a silty-clay soil, widespread in Central Italy. The tests were carried out with the aim of selecting the most energy-efficient imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…On the other hand, a study confirmed that a biomass coverage index of 43.8% represents the best performance of disking operations [76]. Similarly in our study, a higher DM of 2YC red clover in DP treatment was observed (Figure 5b) and could be accurately predicted.…”
Section: The Impact Of the Cultivated Period Flight Times And Farming Operationssupporting
confidence: 89%
“…On the other hand, a study confirmed that a biomass coverage index of 43.8% represents the best performance of disking operations [76]. Similarly in our study, a higher DM of 2YC red clover in DP treatment was observed (Figure 5b) and could be accurately predicted.…”
Section: The Impact Of the Cultivated Period Flight Times And Farming Operationssupporting
confidence: 89%
“…In Italy, the most common conventional method adopted in silty-clay soils to prepare the seedbed is based on the chopping (rarely the burning) of the residues from previous crops, on a deep ploughing (0.30-0.40 m) aimed at burying the residues [8], and on Sustainability 2021, 13, 6506 2 of 19 secondary tillage by means of machines with working tools operated by the tractor's Power Take-Off (PTO), such as power harrow or rotary tiller [9,10]. Unwanted effects of such methods can be excessive energy requirements [11], and related costs [12], due to high PTO torque needed to drive the rotors, worsening of soil structure due to compaction which leaves the soil susceptible to crusting and affects plant growth and yield, loss of nutrients in deeper layers, mineralization of organic matter in upper layers, increasing soil erosion caused by wind and runoff [13]. Moreover, much research has shown that high working speed and deep tillage results in greater tractor's CO 2 emissions [14,15], due to high fuel consumption [16], and favourable conditions for microbiological activity created by the deep tillage [17].…”
Section: Introductionmentioning
confidence: 99%
“…The most severe traction conditions for agricultural tires depend on the characteristics of the ground surface and generally occur in the interval 0 to 2.8 m s −1 (for example in primary soil tillage) and decrease for increasing velocities [36,37]. The tests were carried out within this interval.…”
Section: Travel Speedmentioning
confidence: 99%